Magnetic coupling in highly-ordered NiO/Fe3O4(110): ultrasharp magnetic interfaces vs. long-range magnetoelastic interactions - Krug, Ingo Peter; Haverkort, Maurits W. (Arxiv, 2008)
We present a laterally resolved X-ray magnetic dichroism study of the magnetic proximity effect in a highly ordered oxide system, i.e. NiO films on Fe3O4(110). We found that the magnetic interface shows an ultrasharp electronic, magnetic and structural transition from the ferrimagnet to the antiferromagnet. The monolayer which forms the interface reconstructs to NiFe2O4 and exhibits an enhanced Fe and Ni orbital moment, possibly caused by bonding anisotropy or electronic interaction between Fe and Ni cations. The absence of spin-flop coupling for this crystallographic orientation can be explained by a structurally uncompensated interface and additional magnetoelastic effects.